The Effect of Discipline and Learning Motivation on Student Learning Outcomes in Elementary Schools - Salma Attakhidijah; Muhroji (Universitas Pendidikan Ganesha, 2022)
Discipline and learning motivation of students are factors that can affect student learning outcomes at school. Based on the results of observations, it shows that the discipline and learning motivation of fifth-grade students is not optimal and still need to be improved. This study aims to analyze the effect of discipline and learning motivation on the learning outcomes of high school students in elementary schools. The method used is a quantitative method with a correlational design. The population in this study were high school students in elementary school with a sample of 30 students. The data collection technique was carried out using a questionnaire based on the results of the discipline instrument and learning motivation with a Likert scale score of 1 to 4, while the data in the form of learning outcomes were obtained from their respective teachers in the form of PTS scores for the second semester. In this study, the data analysis technique used was the normality test and hypothesis testing with Microsoft Excel 2019. The results showed that there was an influence of learning discipline on the learning outcomes of high-class students. Then there is the influence of learning motivation on the learning outcomes of high-grade students in elementary school. There is an influence of discipline and learning motivation in the learning outcomes of high-grade students in elementary schools.